Implications of ICNIRP 2020 Exposure Guidelines on the RF EMF Compliance Boundary of Base Stations - Colombi, Davide; Xu, Bo; Anguiano Sanjurjo, David; Joshi, Paramananda; Ghasemifard, Fatemeh; Di Paola, Carla; Törnevik, Christer (Frontiers in Communications and Networks, 2022)
In March 2020, the International Commission on Non-Ionizing Radiation Protection (ICNIRP) released its new guidelines (ICNIRP 2020) on the limitation of radio frequency (RF) electromagnetic fields (EMF) exposure in the frequency range 100 kHz–300 GHz. These have taken several years to develop and include the review of the latest scientific literature. Most countries worldwide currently apply the RF-EMF exposure limits provided in the ICNIRP 1998 guidelines and are expected to align their regulations according to the recently revised limits. In this paper, the implications of the ICNIRP 2020 guidelines on the RF-EMF compliance of base stations (BSs) for mobile communications are analyzed in detail. The study covers different types of BS products, from low-power small cells to macro cell equipment, operating within different frequency bands and of relevance for 2G to 5G mobile technologies. A direct comparison of the BS RF-EMF exclusion zones (or compliance boundaries), when the ICNIRP 2020 and the ICNIRP 1998 limits are applied, is provided. Since existing and future mobile equipment infrastructure is likely to be required to comply with the ICNIRP 2020 guidelines, the paper provides useful information to mobile equipment manufacturers, mobile operators, standardization bodies and regulators.